Multidirectional Networks of Government Transparency: A Preliminary Model (Jurnal Bina Praja, 2016)
This article reviews some literature in theoretical level regarding two concepts: governance network and government transparency, in order to search for theoretical linkages and to build an alternative framework that can support the implementation of public disclosure. Transparency agenda has been implemented in various forms at international, national, and local level. Transparency application was also followed by Indonesia with the implementation of Public Information Disclosure Law since 2008. This enthusiasm is quite reasonable because transparency is believed to be one of the human rights principles; as well as a key to better governance, that can help democracy consolidation, prevent corruption, strengthen the legitimacy and improve efficiency. In order to maximize transparency, the government can use a network approach because of some changes at this time, such as democratization, decentralization, and liberalization has placed the government in a position where there is not one actor who manages the state power without stakeholder’s participation. In this context, the government needs to build synergies with other institutions in a reciprocal relationship with all stakeholders. Therefore, adopting the theory of government networks can be one of the strategies to strengthen government transparency. The findings of this article indicate that the government transparency application needs to develop networks in all directions: intragovernmental, intergovernmental and collaborative networks. These three types of network in contrast with the popular belief that government transparency is interpreted only as a procedural activity to outside parties. A preliminary model in this article gives an overview about the arena of government transparency with multi-directional networks more comprehensively.
Keywords: governance network; network approach; government transparency